Developing an executive learning community: Focus on collective creation - Lepistö Tanja Tuulikki; Hytti Ulla (Academy of Management, 2022)
The preoccupation within executive education with addressing relevance and resource constraints, with developing the capacity of participants to become reflexive practitioners, and with sustaining long-lasting change in organizations calls for new innovations and formats for executive education. Building on theories of the collective creation of value and learning communities, and employing a methodology based on narrative ethnography, we empirically investigated how collective creation is facilitated to develop a learning community in executive education with a longitudinal study of learning camps. The study demonstrated how improvisational theater activities can strengthen collective creation to foster the development of a learning community and how the sense of community supports collective creation. The study develops a framework for developing executive learning communities.